2017
DOI: 10.1159/000479847
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Associated Plasma Protein A2 in Hemodialysis Patients: Significance for Prognosis

Abstract: Background: Pregnancy-associated plasma protein A (PAPP-A) is associated with adverse outcome of long-term hemodialysis patients (HD). The aim of the study was to test whether its homolog pregnancy-associated plasma protein A2 (PAPP-A2) can be detected in serum of HD patients and to define its significance. Methods: The studied group consisted of 102 long-term HD patients and 25 healthy controls. HD patients were prospectively followed up for five years (2009-2014). PAPP-A2 was measured by surface plasmon reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…They also measured PAPP-A2 with an SPR biosensor in long-term hemodialysis patients, and found that PAPP-A2 was increased in these patients. 4 In our previous study, we further demonstrated that a functionalized GO-based SPR biosensor had higher sensitivity, affinity and selective ability for PAPP-A2 than a traditional SPR biosensor. In this pilot study, we first used a GO-based SPR biosensor to simultaneously measure PAPP-A and PAPP-A2.…”
Section: Mixed Sample Investigation and Interference Test With The Gomentioning
confidence: 86%
See 3 more Smart Citations
“…They also measured PAPP-A2 with an SPR biosensor in long-term hemodialysis patients, and found that PAPP-A2 was increased in these patients. 4 In our previous study, we further demonstrated that a functionalized GO-based SPR biosensor had higher sensitivity, affinity and selective ability for PAPP-A2 than a traditional SPR biosensor. In this pilot study, we first used a GO-based SPR biosensor to simultaneously measure PAPP-A and PAPP-A2.…”
Section: Mixed Sample Investigation and Interference Test With The Gomentioning
confidence: 86%
“…Previous studies using traditional SPR biosensors to measure various types of antigen-antibody reactions of PAPP-A and PAPP-A2 have shown promising results (Table 1). 4,[25][26][27][28][29][30] Mikkelsen et al 25 used SPR biosensors to assess the binding of pituitary adenylate cyclase-activating polypeptide type 1 (PAC1) receptor, a monoclonal single-chain fragment variable (scFv) antibody, to immobilize PAPP-A in the presence of calcium ions. They also investigated interactions between PAPP-A and recombinant antibodies PAC1-D8-scFv or PAC1-D8-mIgG2a in multiple animal species using SPR biosensors.…”
Section: Mixed Sample Investigation and Interference Test With The Gomentioning
confidence: 99%
See 2 more Smart Citations